2016
DOI: 10.18203/issn.2455-4510.intjresorthop20164787
|View full text |Cite
|
Sign up to set email alerts
|

Distally based reverse sural artery flap as an interpolation flap

Abstract: Background: Coverage of soft tissue defects of the foot and ankle has imposed a challenging situation to the plastic surgeon. Some patients have contraindications for microsurgery, thus limiting the options for local tissue transfer. The Reverse sural artery flap is frequently used for reconstruction of distal third leg, ankle, and heel. The major disadvantage of RSA flap is compression of pedicle within subcutaneous tunnel leading to venous congestion and distal flap necrosis. To overcome this problem, we des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In this study, a reverse sural artery flap was used, which has been proven to be clinically effective in treating defects in the distal lower extremities, such as the tibia ankle and heel defects [23,24]. Similar to the results of this study, several studies have shown good results with the procedure in the lower limbs [25][26][27]. This procedure is a myofascial skin flap based on the sural artery network; therefore, unlike the free flap, it does not require microsurgery using a microscope, making the procedure simple.…”
Section: Discussionsupporting
confidence: 57%
“…In this study, a reverse sural artery flap was used, which has been proven to be clinically effective in treating defects in the distal lower extremities, such as the tibia ankle and heel defects [23,24]. Similar to the results of this study, several studies have shown good results with the procedure in the lower limbs [25][26][27]. This procedure is a myofascial skin flap based on the sural artery network; therefore, unlike the free flap, it does not require microsurgery using a microscope, making the procedure simple.…”
Section: Discussionsupporting
confidence: 57%